No detection of c-kit gene mutations in exons 9, 11, 13 and 17 and low CD117 expression in plaque-stage mycosis fungoides - David Aldo De Luca; Paula Andrea Enz; Ricardo Luis Galimberti; Adriana Raquel Rinflerch (Anais Brasileiros de Dermatologia, 2018)
Abstract: The growth factor receptor c-kit (CD117) is expressed in immature T-cells and in some advanced forms of mycosis fungoides. c-kit gene mutation results in unrestricted neoplastic proliferation. We aimed to detect by PCR the most frequent exon mutations in seventeen plaque-stage MF patients, in their perilesional skin and in healthy skin donors. We secondarily evaluated CD117 expression by immunohistochemistry in plaque-stage and tumor-stage MF. We detected no mutation in c-kit gene and low CD117 expression was confirmed on atypical cells in one patient. Complete c-kit exon and intron sequences should be assessed and more sensitive sequencing method could be also applied.